2014
DOI: 10.1016/j.neuropharm.2014.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Differences in amyloid-β clearance across mouse and human blood–brain barrier models: Kinetic analysis and mechanistic modeling

Abstract: Alzheimer’s disease (AD) has a characteristic hallmark of amyloid-β (Aβ) accumulation in the brain. This accumulation of Aβ has been related to its faulty cerebral clearance. Indeed, preclinical studies that used mice to investigate Aβ clearance showed that efflux across blood-brain barrier (BBB) and brain degradation mediate efficient Aβ clearance. However, the contribution of each process to Aβ clearance remains unclear. Moreover, it is still uncertain how species differences between mouse and human could af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
138
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(153 citation statements)
references
References 45 publications
15
138
0
Order By: Relevance
“…By contrast, our experiments evaluated functional Ab and apoE interactions under a variety of conditions. Murine and human ECs also differentially clear Ab with a 30-fold increase of Ab uptake in mouse cells (Qosa et al, 2014). Together, these observations might explain the differences observed between previously published murine data and our human model.…”
Section: Discussionsupporting
confidence: 67%
“…By contrast, our experiments evaluated functional Ab and apoE interactions under a variety of conditions. Murine and human ECs also differentially clear Ab with a 30-fold increase of Ab uptake in mouse cells (Qosa et al, 2014). Together, these observations might explain the differences observed between previously published murine data and our human model.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have suggested that ~60% of brain Aβ is cleared via transportation to the periphery 21,22 . Our group has demonstrated, in a mouse model of AD, that brain-derived Aβ can be physiologically cleared in the periphery, and that a singular peripheral system can remove ~40% of the Aβ produced in the brain 23 .…”
Section: Central and Peripheral Clearance Of Aβmentioning
confidence: 99%
“…On the other hand, Aβ circulating in the blood can influx into and/or efflux from the brain, through a receptor-mediated transport, mechanism by which Aβ crosses the blood brain barrier (BBB). [16][17] There are a wide variety of methodologies for the measurement of products of cellular processes in CSF, blood plasma and serum as biomarkers for the diagnosis of different diseases and disorders.…”
Section: Introductionmentioning
confidence: 99%